The Value of Nationalism in the Turbulent Script of Away Enawar's Collection of Rhymes to the Torn Heart and Its Relevance to Literature Learning in High School - Iqbal, Muhamad; Anggraini, Nori; Sulaeman, Agus (Universitas Muhammadiyah Tangerang, 2023)
The value of nationalism is very important for the life of the nation and state, especially for the next generations of the nation, because this value is a manifestation of love and honor for their own nation. With that, the younger generation can do something best for their nation, maintain the integrity of national unity and unity and increase the dignity of the nation so as not to threaten and destroy the integrity of the Indonesian nation. Therefore, the application of nationalism values in the educational environment is very important to be instilled in students such as habituation to maintain the good name of the school, singing the national anthem, the use of good and correct Indonesian, and respect for the red and white flag